Sleep quality in patients with dental anxiety. (February 2015) - Almoznino, Galit; Zini, Avraham; Sharav, Yair; Shahar, Adi; Zlutzky, Hulio; Haviv, Yaron; Lvovsky, Alex; Aframian, Doron J.
Abstract: Background: Psychological distress is associated with sleep disturbances; however there is little research on sleep quality in dental anxiety (DA) patients. Objectives: To measure the sleep quality in patients with DA compared to patients with an exacerbated gag reflex (GAG) and controls and to analyze its association with various demographic and behavioral parameters. Methods: 67 DA patients, 54 GAG patients and 100 controls with no history of DA or GAG participated in the study. Data regarding: demographic details, smoking habits, the Pittsburgh Sleep Quality Index (PSQI), Numeric Rating Scale (NRS) for pain assessment, Corah's dental anxiety scale (DAS) and Oral Health Impact Profile-14 (OHIP-14), plaque index (PI) and Decay, Missing and Filled Teeth (DMFT) scores were collected. Results: 49.3% of the DA group and 38.9% of the GAG group were poor sleepers (mean PSQI score > 5), compared to 29.0% of the controls (PSQI mean scores: 5.8 ± 3.4, DA group; 5.2 ± 3.6 GAG group vs. 4.5 ± 2.7, control group; p  = 0.029). Compared to controls, DA and GAG patients exhibited poorer scores in the sleep disturbances PSQI component ( p  = 0.001). DA patients exhibited poorer scores in the sleep duration PSQI component compared to the control ( p  = 0.002) and GAG groups ( p  = 0.033). Female gender ( p  = 0.039), higher current ( p  = 0.046) and maximal NRS ( p  = 0.019), higher DAS ( p  < 0.001) and OHIP-14 ( p  < 0.001) scores and more missing teeth ( p  = 0.003) were positively associated with higher PSQI scores. Conclusions: DA patients suffered more from impaired sleep than controls and GAGs. Impaired sleep in DA patients is multidimensional phenomenon influenced by the specific diagnosis, gender, pain, dental anxiety levels, dental experience and oral health related quality of life. Highlights: Dental anxiety (DA) is a health problem affecting 5–20% of adult populations. DA patients exhibited impaired sleep compared to controls and patients with gagging. Impaired sleep in DA patients is multidimensional phenomenon. Clinicians & health authorities should be aware of the unique characteristics of DA.